Enhanced photo-induced charge separation and solar-driven photocatalytic activity of g-C3N4 decorated by SO42−. (December 2015) - Zhong, Junbo; Li, Jianzhang; Liu, Xinlu; Wang, Qizhao; Yang, Hao; Hu, Wei; cheng, Chaozhu; Song, Jiabo; Li, Minjiao; Jin, Tian
Abstract: SO4 2− decorated g-C3 N4 with enhanced photocatalytic performance was prepared by a facile pore impregnating method using (NH4 )2 S2 O8 solution. The photocatalysts were characterized by the Brunauer–Emmett–Teller (BET) method, X-ray diffraction (XRD), scanning electron microscopy (SEM), UV–vis diffuse reflectance spectroscopy (DRS), transmission electron microscopy (TEM), Fourier-transform infrared (FT-IR), X-ray photoelectron spectroscopy (XPS) and surface photovoltage (SPV) spectroscopy, respectively. The separation efficiency of photo-generated charge was investigated using benzoquinone as scavenger. The results demonstrate that sulfating of g-C3 N4 increases the adsorption of rhodamine B on g-C3 N4, the hydroxyl content and the separation efficiency of photo-generated charge. The photocatalytic activity of SO4 2− /g-C3 N4 for decolorization of rhodamine B and methyl orange (MO) aqueous solution was evaluated. The result shows that loading of 6.0 wt% SO4 2− results in the best photocatalytic activity under simulated solar irradiation and SO4 2− play an important role in boosting the photocatalytic activity.